Pharmacological blockade of protease-Activated Receptor 2 improves airway remodeling and lung inflammation in experimental allergic asthma - Natália Alves de Matos; Diego Carlos dos Reis; Lucas Kraemer Rocha; Matheus Silvério de Mattos; Geovanni Dantas Cassali; Remo Castro Russo; Andrea de Castro Perez; André Klein (Universidade de São Paulo, 2023)
Abstract Protease-activated receptors (PARs) are metabotropic G-protein-coupled receptors that are activated via proteolytic cleavage of a specific sequence of amino acids in their N-terminal region. PAR2 has been implicated in mediating allergic airway inflammation. This study aims to study the effect of PAR2 antagonist ENMD1068in lung inflammation and airway remodeling in experimental asthma. Allergic lung inflammation was induced in sensitized BALB/c mice through intranasal instillations of ovalbumin (OVA), and mice were pretreated with ENMD1068 1 hour before each OVA challenge. Bronchoalveolar lavage fluid (BALF) was collected, and the lungs were removed at different time intervals after OVA challenge to analyze inflammation, airway remodeling and airway hyperresponsiveness. Ovalbumin promoted leukocyte infiltration into BALF in a PAR2-dependent manner. ENMD1068 impaired eosinophil peroxidase (EPO) and myeloperoxidase (MPO) activity in the lung parenchyma into BALF and reduced the loss of dynamic pulmonary compliance, lung resistance in response to methacholine, mucus production, collagen deposition and chemokine (C-C motif) ligand 5 expression compared to those in OVA-challenged mice. We propose that proteases released after an allergen challenge may be crucial to the development of allergic asthma in mice, and PAR2 blockade may be useful as a new pharmacological approach for the treatment of airway allergic diseases.